PERANCANGAN WEBSITE DESA LUMBAN PEA TIMUR KECAMATAN BALIGE, KABUPATEN TOBA SEBAGAI MEDIA INFORMASI DAN E-COMMERCE - Stevani Laura Zois Br. Simanjuntak; Marlyna Infryanty Hutapea; Eviyanti Novita Purba; Jamaluddin Jamaluddin (Universitas Methodist Indonesia, 2022)
Lumban Pea Timur Village is one of the villages in Balige District, Toba Regency, North Sumatra Province. In the current development of internet technology, the availability of fast, precise and accurate information is important and needed for Lumban Pea Timur village to distribute information to the village community. Most of the livelihoods of Lumban Pea Timur Village are in the agricultural, plantation and livestock sectors. So far, the sales process in Lumban Pea Timur Village is still done conventionally, this creates difficulties in marketing and promoting the community's business results. The purpose of this research is to help the village community to obtain the latest information in East Lumban Pea Village and assist the community in East Lumban Pea Village in selling their business results to consumers through the village website. The village website designed using the PHP programming language and MySQL database as its database and program testing using black box testing. With the design of the village website, it is hoped that it can help the village community to obtain information and introduce the results of the efforts of the people in the East Lumban Pea Village to the global market so that it can improve the economy in the East Lumban Pea Village, especially the village community.